Asian rice price crisis causes, impacts and implications - Rosegrant, Mark (Asian Journal of Agriculture and Development, 2010)
The world price of rice is still high relative to the 2007 level and is likely to remain too high to be affordable to millions of the poor. Keeping the price of rice low and affordable to the poor is critically important for poverty reduction. Poor people spend a substantial proportion of their incomes on rice. A rise in the price of rice is equivalent to a reduction in their real incomes. The paper provides an analyzes of factors that have contributed to this rapid rise in rice price and assesses the impact of price rise on poverty. A scenario analysis on rice prices is conducted through projection of long-term demand and supply of rice. Short and long-term solutions to the price crisis are recommended. To make long-term projections of rice prices, the authors use the International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT) developed in the early 1990s, revised in 2002 to include the global water simulation model, and updated in 2007 (Rosegrant et al. 1995, 2002, 2008). IMPACT offers a methodology for analyzing baseline and alternative scenarios for global food demand, supply, and prices for agricultural commodities are determined. The country and regional agricultural sub-models are linked through trade, and a global equilibrium is obtained through iteration -- such that the sum of net trade balances is driven to zero for each commodity. The long-term imbalance between the supply and demand for rice is identified as the fundamental cause of the current rice crisis. Yield growth over the past decade or so has been found to have slackened considerably. Long-term projections made in the study indicate that the price of rice will increase substantially unless a major boost in investments in agricultural research and development is made. Productivity growth through increased research investments and the development and dissemination of improved technologies as well as policy reforms are the only long-term viable solution for bringing the prices down and preventing future increases in rice prices. A second green revolution is seen as the means to reverse the rising trend in rice prices and to keep prices low.